Valuing conservation benefits of disease control in wildlife: A choice experiment approach to bovine tuberculosis management in New Zealand's native forests. (15th March 2017) - Tait, Peter; Saunders, Caroline; Nugent, Graham; Rutherford, Paul
Abstract: We assess the non-monetary environmental benefits that accrue incidentally in New Zealand (NZ) from pest management conducted primarily to control an animal disease, bovine tuberculosis (TB). TB is an infectious disease that is one of the world's most serious animal health problems and, in many parts of the developing world, still a major mortality risk for humans. The incidence of TB in New Zealand (NZ) farmed livestock has been reduced progressively over the last 20 years, largely due to extensive and sustained population control of the main wildlife reservoir of disease, the introduced brushtail possum. Possums are also major pests that threaten indigenous forest biodiversity, and so extensive possum control for TB mitigation also incidental benefits conservation, but the extent and public value of this benefit has yet to be quantified. We conducted a choice experiment survey of the NZ public in an effort to value the native forest biodiversity benefits of TB-related possum control. We find strong public support for conservation outcomes consequent to TB-possum control in public native forests. The public place substantial value on the most observable biodiversity benefits of TB possum control, such as improved forest canopies and presence of native birds. The benefits, costs and values of TB-possum control are discussed in relation to the future directives of NZ's TB control programme, which is headed toward first regional and then national level disease eradication. Highlights: Conservation co-benefits of bovine tuberculosis control in New Zealand native forest are valued. Control reduces threats to invertebrates, native birds, forest plants and canopy dieback. The majority of benefit stems from reduced possum browsing of vulnerable tree canopy. Significant public value for overall conservation benefits at $156 per person annually. Non-market economic valuation improves pest management Cost Benefit Analysis.